2000
DOI: 10.1074/jbc.m005384200
|View full text |Cite
|
Sign up to set email alerts
|

Papin

Abstract: A neural plakophilin-related armadillo repeat protein (NPRAP)/␦-catenin interacts with one of Alzheimer disease-related gene products, presenilin 1. We have previously reported the interaction of NPRAP/␦-catenin with synaptic scaffolding molecule, which is involved in the assembly of synaptic components. NPRAP/␦-catenin also interacts with E-cadherin and ␤-catenin and is implicated in the organization of cell-cell junctions. p0071, a ubiquitous isoform of NPRAP/␦-catenin, is localized at desmosomes in HeLa and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…In the previous study, we reported that PAPIN was detected not only at the cell -cell contacts but also on the apical membranes in the bronchial epithelial cells (Deguchi et al, 2000). We first confirmed the apical localization of PAPIN.…”
Section: Papin Is Localized On the Apical Membrane In Madin Darby Cansupporting
confidence: 68%
See 2 more Smart Citations
“…In the previous study, we reported that PAPIN was detected not only at the cell -cell contacts but also on the apical membranes in the bronchial epithelial cells (Deguchi et al, 2000). We first confirmed the apical localization of PAPIN.…”
Section: Papin Is Localized On the Apical Membrane In Madin Darby Cansupporting
confidence: 68%
“…The rabbit anti-p0071 antibodies were described previously (Deguchi et al, 2000). The mouse monoclonal anti-PAPIN antibody was raised against the product of pGex4T-1 PAPIN-15.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Erbin is probably only one component of protein complexes involved in these processes, since other PDZ proteins, including Papin, bind to p0071. Papin, a novel PDZ domain protein, interacts with p0071 in the insoluble fraction of cell extracts, whereas we recover the p0071-Erbin interaction in a 1% Triton X-100 extraction buffer (43). Other studies have shown that protein complexes containing p0071 or ␦-catenin/NPRAP, a p0071-like protein, are extractable by a Tritonbased buffer (44,45).…”
Section: Discussionmentioning
confidence: 84%
“…The carboxylterminal domain of p0071 (along with ARVCF and ␦-catenin) terminates with a PDZ domain-binding motif (30,31) and interacts with the PDZ motif-containing protein PAPIN (59) and with the LAP protein Erbin (57,58). LAP family proteins such as Erbin and Scribble play important roles in the development of cell polarity during morphogenic events in Caenorhabditis elegans and Drosophila (44).…”
Section: P0071 Binds Ve-cadherin and Desmoplakinmentioning
confidence: 99%